Voltage-activated and calcium-activated currents studied in solitary rod inner segments from the salamander retina - Bader, C. R. (1982)
1. Solitary rod inner segments were obtained by enzymatic dissociation of the tiger salamander (Ambystoma tigrinum) retina. Their membrane currents were studied with the single-pipette voltage-clamp technique. Individual currents were isolated with the aid of pharmacological agents. 2. Extracellular caesium blocked a current activated by hyperpolarization from -30 mV. Changing external sodium and potassium concentrations altered the value of the reversal potential in a manner consistent with the current being carried equally by both ions. 3. Extracellular tetraethylammonium (TEA) blocked a current activated by depolarization from -70 mV. In normal medium this current had a reversal potential of -72 mV. Changing the external potassium concentration altered the value of the reversal potential in a manner consistent with the current being carried predominantly by potassium. 4. Extracellular cobalt blocked a current activated by depolarization that had an initial inward and a later outward component. 5. After EGTA was injected into an inner segment the outward component was suppressed. Cobalt then blocked an inward current. This current is believed to be carried predominantly by calcium. The conductance increased with depolarization from -45 mV and reached a maximum at approximately 0 mV. Following a step of depolarization the current activated rapidly (< 20 msec) and then remained constant for at least several seconds without evidence of inactivation. 6. Injecting caesium into an inner segment eliminated a calcium-activated outward current believed to be carried by potassium ions. 7. After the injection of caesium there remained another calcium-activated current with a reversal potential of -17 mV. Changing extracellular chloride concentration altered the value of the reversal potential in a manner consistent with chloride carrying at least 70% of the current. Another anion may carry the balance. 8. When the five currents mentioned in items 2, 3, 5, 6 and 7 were blocked, the membrane resistance between -90 and -25 mV was linear, time-independent, and had a high value (2·1 GΩ). 9. The five identified currents can all be activated in the physiological range of voltage in which salamander rods normally operate.